Technical Efficiency of Rubber Farmers’ in Changwat Sakon Nakhon: Stochastic Frontier Analysis - Kittilertpaisan, Jitti; Kittilertpaisan, Kallaya; Khatiwat, Phakhaphon (International Journal of Economics and Financial Issues, 2016)
The study was conducted to analyze the technical efficiency of smallholding rubber farmers in Changwat Sakon Nakhon. The numbers of 375 smallholding rubber farmers were analyzed using stochastic frontier analysis. The smallholding rubber farmers were sampled using stratified random sampling technique with one output and only three inputs (age of plantation, labor, cultivated aras). Results clearly show that the mean technical efficiency of rubber product in Changwat Sakon Nakhon is 0.69 or 69 percent with the variance of parameters (gamma and sigma squared) of the frontier production function were both significant at p<0.05. However, the inefficiency model revealed that education, training, gender and age of smallholding rubber farmer were found to have significant effect on rubber farmers’ efficiency at p<0.05. Keywords: Technical Inefficiency; Stochastic Frontier; Changwat Sakon Nakhon JEL Classifications: Q12; Q13